Natural resource as absorbent for carbon capture in industrial activities - Segaran, Pravin Segaran (School of Environmental Engineering Universiti Malaysia Perlis, 2011)
Carbon dioxide (CO2) emissions have increased in recent years in the cities of developing countries, due to heavy traffic and low quality fuel. Concentration in the atmospherehere have exceeded the safe limits of limits of 350 ppm since 1988. There is now a general acceptance that increased efforts must be made to reduce industrial sources of this greenhouse gas. In order to test if a significant proportion of carbon could be absorbed by mineral soil, a study was carried out. Therefore this study will investigate the potential of natural resource carbonation using tropical mineral soil to study the capacity of this natural resource to capture carbon dioxide. The carbonation process will be carried out in a fabricated, laboratory-sized reactor to perform an accelerated carbonation by using different mixing spedd temperature, pH adjustment , contact time, gas flow rate, and particle size.